Conceptualización de las medidas preventivas en materia ambiental en el derecho colombiano a partir de la ley 1333 de 2009 frente al principio internacional de precaución (2019)
The healthy environment is a constitutional right of individual and collective application, granted by the institution of the social state of law adopted in the Constitution of 1991, whose exercise of weighting for its defense, is frequently faced with the circumstances raised in favor of economic development and social of the country, evidencing increasingly the exploitation of natural and mineral resources by private entities and mostly foreigners, under the premise of contributing to the increase of gross domestic product and improve the quality of life of citizens. However, in the face of recommendations of origin and international application aimed at anticipating or anticipating the possible disaster situations triggered by the exercise of these activities and inviting countries to safeguard this precious good in order to have a healthier planet, it is a pending question to resolve the sense in which the action of the Colombian legislator is oriented, its wanting to be, to determine if the regulations issued for the prevention of environmental damage are within a really effective margin or if this is established in a scope of application only aimed at operating within the range of completion of the damage to perform its intervention as it pertains, so that through this investigation it is possible to determine its role and scope, which are expected to obey that guarantee of the prevalence of the general interest and the protection of the aforesaid fundamental right.